Pendampingan Hafalan Al-Qur’an Melalui Metode Tikrar Santri Di Ma As Sathi’ - Su’udin Aziz; Farida Isroani (Pusat Riset dan Inovasi Nasional, 2021)
Al-Qur'an as a source, guide, good news and warning and provide benefits for Muslims. In addition to giving goodness and glory to those who read it. If reading it can increase the faith and piety of Muslims. However, if you memorize your intention because of Allah SWT, you can make a noble deed. One of the memorization methods adjusts to the times, namely the pledge method. The pledge method means repeating continuously from short letters to long letters. This research uses descriptive qualitative type so that primary and secondary data are obtained. Primary data conducted observations and interviews with the institution. While secondary data obtained from literature studies from books, documents, internet and others. The results of this study are that the pledge method involves memory activity, repeating verses is easier, fluent and memory sticks more. The implementation of the pledge method is carried out in two stages, namely the preparation stage and the implementation stage of the pledge which can be done facing the teacher or individually. This pledge method is useful for facilitating memory, students so as not to hinder memorization of the Qur'an by means of intention for Allah and reading a lot and repeating memorization.